ANALISIS PENERAPAN PSAK 71 TERKAIT CADANGAN KERUGIAN PENURUNAN NILAI: PADA PERUSAHAAN SEKTOR PERBANKAN BUMN YANG TERDAFTAR DI BEI - Mohamad Husni; Wenny Ariesta Apriliani; Riyanthi Idayu (LP2M Universitas Bina Bangsa, 2022)
PSAK No. 71 is the merger of IFRS 9 whose implementation is calculated on January 1, 2020. PSAK 71 as a new regulation will have a significant impact on banking in Indonesia, especially in calculating CKPN. PSAK 71 introduces a new method, namely the expected loss which is forward-looking. In addition to being forward-looking, this new standard requires reporting entities to include information from past events and current conditions in the expected credit loss (ECL) measurement. This means that banks must provide CKPN in the credit or loan category, which are current, doubtful, or bad. This study aims to analyze the application of PSAK 71 to CKPN on bank credit and capital and bank financial performance in terms of net income before and after the application of the new standard. The method in this study uses a qualitative method with a descriptive design, the research sample is four state-owned banks listed on the IDX. This study found that in the application of PSAK 71, CKPN on bank credit and capital did not necessarily have a negative impact on all banks but on bank profits had a negative impact on all banks